Peer driven or driven peers? A rapid review of peer involvement of people who use drugs in HIV and harm reduction services in low- and middle-income countries - Judy Chang; Shaun Shelly; Machteld Busz; Claudia Stoicescu; Arif Rachman Iryawan; Dinara Madybaeva; Yuri de Boer; Andy Guise (BMC, 2021)
Abstract Introduction Peer involvement of people who use drugs within HIV and harm reduction services is widely promoted yet under-utilised. Alongside political and financial barriers is a limited understanding of the roles, impacts, contexts and mechanisms for peer involvement, particularly in low- and middle-income settings. We conducted a rapid review of available literature on this topic. Methods Within a community-academic partnership, we used a rapid review approach, framed by realist theory. We used a network search strategy, focused on core journals and reference lists of related reviews. Twenty-nine studies were included. We developed thematic summaries framed by a realist approach of exploring interventions, their mechanisms, outcomes and how they are shaped by contexts. Results Reported outcomes of peer involvement included reduced HIV incidence and prevalence; increased service access, acceptability and quality; changed risk behaviours; and reduced stigma and discrimination. Mechanisms via which these roles work were trust, personal commitment and empathy, using community knowledge and experience, as well as 'bridge' and 'role model' processes. Contexts of criminalisation, under-resourced health systems, and stigma and discrimination were found to shape these roles, their mechanisms and outcomes. Though contexts and mechanisms are little explored within the literature, we identified a common theme across contexts, mechanisms and outcomes. Peer outreach interventions work through trust, community knowledge and expertise, and 'bridge' mechanisms (M) to counter criminalisation and constraining clinic and service delivery environments (C), contributing towards changed drug-using behaviours, increased access, acceptability and quality of harm reduction services and decreased stigma and discrimination (O). Conclusion Peer involvement in HIV and harm reduction services in low- and middle-income settings is linked to positive health outcomes, shaped by contexts of criminalisation, stigma, and resource scarcity. However, peer involvement is under-theorised, particularly on how contexts shape mechanisms and ultimately outcomes. Efforts to study peer involvement need to develop theory and methods to evaluate the complex mechanisms and contexts that have influence. Finally, there is a need to expand the range of peer roles, to embrace the capacities and expertise of people who use drugs.